2011
DOI: 10.3109/0886022x.2010.541586
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Prostaglandin E1 on Renal Microvascular Injury in Rats of Acute Aristolochic Acid Nephropathy

Abstract: Background: To investigate the renal microvascular injury in acute aristolochic acid nephropathy (AAN) and the protective effects of prostaglandin E1 (PGE1) in acute AAN. Methods: Female Sprague-Dawley rats were randomly divided into three groups. The rats in PGE1 group received Caulis Aristolochia manshuriensis (CAM) decoction by gavage for 5 days, and PGE1 was given by vena caudalis before gavage. The rats in model group were gavaged with CAM for 5 days, and the same dose of 0.9% physiologic saline was given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…However, the onset of these drugs needs at least 4–5 years 23 and the benefit seems limited 24 . Recent studies showed that PGE1 had protective effects on renal function by reducing vascular resistance in ischemia-reperfusion 25 , inhibiting the production of transforming growth factor-β (TGF-β) and interleukin-1 (IL-1) in immune-mediated glomerular disease 26 , and increasing microvessel density in acute toxic renal injury 27 . But it is currently unclear if PGE1 could be used for preventing the progression of DN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the onset of these drugs needs at least 4–5 years 23 and the benefit seems limited 24 . Recent studies showed that PGE1 had protective effects on renal function by reducing vascular resistance in ischemia-reperfusion 25 , inhibiting the production of transforming growth factor-β (TGF-β) and interleukin-1 (IL-1) in immune-mediated glomerular disease 26 , and increasing microvessel density in acute toxic renal injury 27 . But it is currently unclear if PGE1 could be used for preventing the progression of DN.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings provide further evidences that PGE1 contributed to improve renal dysfunction in T2DM patients 48 . The renoprotective role of PGE1 has also been reported extensively in the treatment of ischemic renal reperfusion injury, toxic kidney injury, immune-mediated glomerular injury, and contrast-induced nephropathy, consequently resulting in slow progression of ESRD 27 , 49 – 51 . Thus, the present study provided new mechanisms for renoprotective role of PGE1 in clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…The serum creatinine (Scr) was measured using a picric acid method and blood urea nitrogen (BUN) was measured using a urease assay as previously described ( 20 , 21 ). Serum was obtained from blood samples collected in non-heparinized vacuum tubes, then centrifuged at 3,500 x g for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…In a Sprague-Dawley rat model of AAN, treatment with PGE1 increased vascular endothelial growth factor (VEGF) expression and microvascular density. PGE1 also prevented capillary loss and relieved hypoxia, resulting in kidney protection against AA-induced nephrotoxicity [110].…”
Section: Other Agentsmentioning
confidence: 98%